Peningkatan Kemampuan Perawat dalam Interpretasi EKG Normal dan Aritmia dengan Metode Angka 3 - Ii Ismail; Dewi Purnamawati; Wati Jumaiyah; Fitrian Rayasari (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of the number 3 method on nurses' ability to interpret normal ECG and arrhythmias. The research method used a quasi-experimental design with one group pre-test and a post-test with a control group. The results showed that there was a significant difference in the mean score of nurses in the interpretation of normal ECG and arrhythmias in both the intervention and control groups (p-value 0.007 and 0.002). The multiple linear regression test showed that the treatment variable contributed to the nurse's ability to interpret normal ECG and arrhythmias with a p-value of 0.002 with a negative linear pattern (Nurses' ability = 66.099 - 9.156 (treatment). In conclusion, there is a significant difference in the average score of nurses in interpretation. Normal ECG and arrhythmia in both the intervention and control groups. However, the intervention group with the number 3 method had a greater difference in mean values ​​than the control group. Statistically, the more research treatments, the nurses' ability to interpret normal ECG and arrhythmias would decrease. Keywords: Arrhythmia, Normal EKG, Interpretation of ECG, Number Method 3